The efficacy of antidepressants for generalized anxiety disorder: a systematic review and meta-analysis - Schmitt, Ricardo; Gazalle, Fernando Kratz; Lima, Maurício Silva De; Cunha, Ângelo; Souza, Juliano; Kapczinski, Flávio (Associação Brasileira de Psiquiatria, 2005)
OBJECTIVE: To investigate the efficacy and acceptability of antidepressants in the treatment of generalized anxiety disorder. METHODS: All randomized controlled trials assessing the use of antidepressants in generalized anxiety disorder up to may 2002 were included. Non randomized trials and those that included patients with both generalized anxiety disorder and another Axis I co-morbidity were excluded. Relative risks, weighted mean difference and number needed to treat were estimated. People who died or dropped out were regarded as having had no improvement. RESULTS: Antidepressants (imipramine, venlafaxine and paroxetine) were found to be superior to placebo in treating generalized anxiety disorder. The calculated number needed to treat for antidepressants in generalized anxiety disorder was 5.15. Dropout rates did not differ between antidepressants and placebo. CONCLUSION: The available evidence suggests that antidepressants would probably be a reasonable treatment for generalized anxiety disorder patients in the clinical context.

OBJETIVOS: Investigar a eficácia e tolerabilidade dos antidepressivos no tratamento do Transtorno de ansiedade generalizada (TAG). MÉTODOS: Todos os ensaios clínicos randomizados que investigavam o uso de antidepressivos para Transtorno de ansiedade generalizada até maio de 2002 foram incluídos nesta revisão. Ensaios clínicos não randomizados e aqueles que incluíram pacientes com Transtorno de ansiedade generalizada e outra comorbidade de Eixo I foram excluídos. Riscos relativos, diferenças de médias e número necessário para tratar (NNT) foram estimados. Pessoas que morreram ou saíram dos estudos foram considerados como sem melhora. RESULTADOS: Antidepressivos (imipramina, venlafaxina e paroxetina) foram superiores ao placebo no tratamento do Transtorno de ansiedade generalizada. O número necessário para tratar para os antidepressivos em Transtorno de ansiedade generalizada foi 5,15. Taxas de abandono não diferiram entre antidepressivos e placebo. CONCLUSÃO: A evidência disponível sugere que os antidepressivos são um tratamento adequado para pacientes com Transtorno de ansiedade generalizada.
A eficácia dos antidepressivos para transtorno de ansiedade generalizada: uma revisão sistemática e metanálise
Keywords: Anxiety disorders; Antidepressive agents; Randomized controlled trials; Review, academic [Publication type]; Meta-analysis; Transtornos da ansiedade; Agentes antidepressivos; Ensaios controlados aleatórios; Revisão acadêmica [Tipo de publicação]; Metanálise